Alternative measures of the Federal Reserve Banks' cost of equity capital - Michelle L. Barnes; Jose A. Lopez (Federal Reserve Bank of Boston, 2005)
The Monetary Control Act of 1980 requires the Federal Reserve System to provide payment services to depository institutions through the twelve Federal Reserve Banks at prices that fully reflect the costs a private-sector provider would incur, including a cost of equity capital (COE). Although Fama and French (1997) conclude that COE estimates are woefully and unavoidably imprecise, the Reserve Banks require such an estimate every year. We examine several COE estimates based on the Capital Asset Pricing Model (CAPM) and compare them using econometric and materiality criteria. Our results suggest that the benchmark CAPM applied to a large peer group of competing firms provides a COE estimate that is not clearly improved upon by using a narrow peer group, introducing additional factors into the model, or taking account of additional firm-level data, such as leverage and line-of-business concentration. Thus, a standard implementation of the benchmark CAPM provides a reasonable COE estimate, which is needed to impute costs and set prices for the Reserve Banks' payments business.
Keywords: G11; G28; 330; cost of equity; return on equity; CAPM; payments system; Kapitalkosten; Zahlungsverkehr; Zentralbank; Messung; Capital Asset Pricing Model; USA